The First Woman Lead Welder of the Philippines: Elizabeth Espina Borja - Plaza, Leonides "Daisy" Borja (Review of Women's Studies; Vol 8 No 2 (1998): Review of Women's Studies Volume VIII, Number 2 (July-December 1998))
---